Kendala Pustakawan UPT Perpustakaan Universitas Hasanuddin Ketika Work from Home Selama Pandemi COVID-19 - Iskandar Iskandar; Trimurtiati Trimurtiati (Perpustakaan Nasional, 2021)
This study aims to identify and describe the constraints faced by librarians of the Hasanuddin University Library when working from home (WFH) during the COVID-19 pandemic. This research is descriptive. Respondents of this study were librarians of the Hasanuddin University Library who carried out official duties in the field of librarianship at home including doing WFH during the COVID-19 pandemic, starting from the Procurement, Processing, Service, and Information and Technology units. There were two librarians representing each unit as informants, so that eight informants were obtained. Data collection was carried out by distributing questionnaires and documentations. Data were analyzed using qualitative analysis. The results of the study illustrate that the constraints faced by librarians of the Hasanuddin University Library when WFH during the COVID-19 pandemic occurred when: the librarian's view of librarian duties was ineffective; the librarian's ability to work from home was not in accordance with the ability to work in an office; there is no motivation to work at home because the librarian work is supposed to be done offline; the need for facilities and infrastructure is inadequate;and there is no leadership support while working from home. In conclusion, the constraints faced by librarians of Hasanuddin University Library when WFH during the COVID-19 pandemic need to be followed up by providing solutions. The solutions can be made in accordance with the obstacles faced, for example the completeness of facilities and infrastructure and avoiding offline work.